Islamic Religious Education Learning Based on the Development of Student Morals at State Senior High School - Umratul Fajri; Fakhr Aldeen Yahia Osman; Almira Amilbangsa Hadji (Jurnal Pendidikan Agama Islam Indonesia (JPAII), 2024)
Purpose of the study: This study aims to describe the learning of Islamic Religious Education in fostering students' morals, students' moral conditions, and supporting and inhibiting factors at Bantaeng 1 State Senior High School. This study uses a descriptive method with a qualitative approach, using primary and secondary data as the main sources. Methodology: The data collection methods in this study are observation, interviews and documentation. The data analysis techniques used are data collection, data reduction, data presentation and drawing conclusions. Main Findings: The results of the study indicate that Islamic Religious Education learning at Bantaeng 1 State Senior High School fosters students' morals through providing materials (honesty, obeying rules, competing in goodness, working hard, being devoted), teacher role models (discipline, honesty, responsibility, mutual respect), and habits (congregational prayer, religious lectures, guidance in reading the Qur'an). Students' morals are considered good, reflected in the attitude of respecting teachers, mutual respect, protecting the environment, and themselves. Supporting factors for fostering morals include school programs, extracurricular activities, regulations, and teacher competence, while the obstacles are limited learning time and the influence of the school and community environment. Novelty/Originality of this study: The novelty of this research lies in the integration between religious education and student character development, as well as its application in the local context by providing new insights into Islamic Religious Education learning that focuses on morals.